Cardiotoxicity - Wenyong Tan (IntechOpen, 2018)
Cardiotoxicity may be caused by radiotherapy and/or anticancer agents for many malignancies, adverse effects of some drugs in the context of medical intervention or heavy metal intake, especially during the anticancer therapy. This book intends to bring forward the recent development in toxicities from cancer treatment. It updates the possible mechanisms of cardiotoxicities of some anticancer agents and the suggested prevention and treatment strategies. This book contains many valuable contributions from the researchers in oncology and cardiology as well as the clinicians who are experts in this field.
English
Keywords: Medicine; Cardiology and Cardiovascular Medicine; Cardiac Electrophysiology; Health Sciences